2017
DOI: 10.1186/s13195-017-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive profile in prodromal dementia with Lewy bodies

Abstract: BackgroundCortical and subcortical cognitive impairments have been found in dementia with Lewy bodies (DLB). Roughly, they comprise visuoconstructive and executive dysfunction, whereas memory would remain relatively spared. However, the cognitive profile of patients with prodromal DLB remains poorly illustrated to date.MethodsWe included 37 patients with prodromal DLB (age 67.2 ± 8.6 years, 18 men, Mini Mental State Examination [MMSE] score 27.4 ± 2) and 29 healthy control subjects (HCs; age 68.8 ± 7.9 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
64
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 60 publications
10
64
1
1
Order By: Relevance
“…These results, along with the absence of a significant difference in the VOSP scores, might be explained by the relatively low severity of cognitive impairment in our DLB and AD patients at the group level: their mean MMSE scores were, respectively, 24.4 ± 4 and 24.1 ± 5, which usually corresponds to the limit between the prodromal and dementia stages. Indeed, according to Kemp et al [11], visuoperceptual impairments are more likely to occur at the dementia stage. As an illustration, Calderon et al [10] used the same fragmented letters task in their neuropsychological study, with DLB and AD groups whose mean MMSE scores were 20.0 and 21.4 (respectively), and they observed a significantly lower performance in the DLB patients compared to the AD and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results, along with the absence of a significant difference in the VOSP scores, might be explained by the relatively low severity of cognitive impairment in our DLB and AD patients at the group level: their mean MMSE scores were, respectively, 24.4 ± 4 and 24.1 ± 5, which usually corresponds to the limit between the prodromal and dementia stages. Indeed, according to Kemp et al [11], visuoperceptual impairments are more likely to occur at the dementia stage. As an illustration, Calderon et al [10] used the same fragmented letters task in their neuropsychological study, with DLB and AD groups whose mean MMSE scores were 20.0 and 21.4 (respectively), and they observed a significantly lower performance in the DLB patients compared to the AD and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation also included various subtests from the VOSP battery: number location, cube analysis, object decision, silhouettes, dot position. For a comprehensive description of the different neuropsychological assessments, see Kemp et al [11]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 In contrast to MCI as a result of AD (MCI-AD), research on MCI as a result of Lewy bodies (MCI-LB) is limited. 4 Some cross-sectional studies suggest that the cognitive profile of MCI-LB differs from MCI-AD, with less pronounced memory impairment, 8 but lower performance in attention, 3,9 executive, 8,10 and visuospatial functions. 10,11 Other studies in MCI-LB found prominent neuropsychiatric symptoms (NPS), with frequent anxiety, apathy, and sleep disturbances.…”
mentioning
confidence: 99%
“…4 Some cross-sectional studies suggest that the cognitive profile of MCI-LB differs from MCI-AD, with less pronounced memory impairment, 8 but lower performance in attention, 3,9 executive, 8,10 and visuospatial functions. 10,11 Other studies in MCI-LB found prominent neuropsychiatric symptoms (NPS), with frequent anxiety, apathy, and sleep disturbances. 3,8 Only a few longitudinal studies on MCI-LB have been described.…”
mentioning
confidence: 99%